(untitled) (Scientific journal of the Fergana State University, 2024)
In the article, the synthesis of complex-forming sorbents containing nitrogen and oxygen, the properties of complex compounds of some 3d metals based on the obtained sorbents were studied. Complex forming. was studied based on the use of semi-empirical quantum-chemical methods in the study of competing donor centers of coordination of polydentate ligands. The electronic structure, geometric and energetic characteristics of synthesized polymer ligands were studied using quantum chemical methods (Avogadro, Hyper Chem 8.01, GaussView 6.0.16 software). When bond lengths change from a free molecule to a coordinated molecule, a significant change in bond distances is observed. The values ​​of the effective charge of donor atoms in KFQ sorbent molecules are presented on the basis of the table. Comparing the values ​​of electronic charges calculated using these methods, it was concluded that the donor atoms with the highest value of negative charge in all calculated molecules can be coordinated.